Mesenteric desmoid tumor after laparoscopic resection of stage I endometrial cancer: A case report - Mamiko Kusaka; Tetsuo Maeda; Kazuhiro Kitajima; Homare Murakoshi; Takahiro Watanabe; Shigeki Yoshida; Yuka Sano; Noriko Osumi; Mieko Inagaki (Case Reports in Women's Health)
Mesenteric desmoid tumors (DTs) are rare, and there are no specific imaging features that can aid definitive diagnosis. This article presents the case of a 61-year-old woman found to have intra-abdominal DT located in the mesentery at two-year follow-up after laparoscopy-assisted anterior resection for stage I endometrial cancer. Computed tomography (CT) indicated the presence of a solitary tumor arising from the intestinal wall or mesentery. Subsequent magnetic resonance imaging and integrated positron emission tomography/CT with 2-18F-fluoro-2-deoxy-d-glucose suggested DT rather than recurrence, but surgical resection was chosen after considering the potential risks. Surgery confirmed the diagnosis, revealing a tumor at the level of the jejunal mesentery and approximately 5 cm in diameter. The mesenteric tumor was resected, along with part of the jejunum and the greater omentum. Histopathological examination of the surgical specimens confirmed the diagnosis of DT. As mesenteric DT after laparoscopic resection of stage I endometrial cancer is rare, a high degree of suspicion is necessary for diagnosis. Given that laparoscopic surgery is increasingly used in gynecological clinical practice, gynecologists and radiologists should be aware that DT should be considered in the differential diagnosis when a mesenteric mass is detected during follow-up after a surgical procedure, including laparoscopy.